Modeling nonalcoholic fatty liver disease on a liver lobule chip with dual blood supply. (15th October 2021) - Du, Kun; Li, Shibo; Li, Chengpan; Li, Ping; Miao, Chunguang; Luo, Tianzhi; Qiu, Bensheng; Ding, Weiping
Abstract: Nonalcoholic fatty liver disease (NAFLD) has emerged as a public health concern. To date, the mechanism of NAFLD progression remains unclear, and pharmacological treatment options are scarce. Traditional animal NAFLD models are limited in helping address these problems due to interspecies differences. Liver chips are promising for modeling NAFLD. However, pre-existing liver chips cannot reproduce complex physicochemical microenvironments of the liver effectively; thus, NAFLD modeling based on these chips is incomplete. Herein, we develop a biomimetic liver lobule chip (LC) and then establish a more accurate on-chip NAFLD model. The self-developed LC achieves dual blood supply through the designed hepatic portal vein and hepatic artery and the microtissue cultured on the LC forms multiple structures similar to in vivo liver. Based on the LC, NAFLD is modeled. Steatosis is successfully induced and more importantly, changing lipid zonation in a liver lobule with the progression of NAFLD is demonstrated for the first time on a microfluidic chip. In addition, the application of the induced NAFLD model has been preliminarily demonstrated in the prevention and reversibility of promising drugs. This study provides a promising platform to understand NAFLD progression and identify drugs for treating NAFLD. Statement of significance: Liver chips are promising for modeling nonalcoholic fatty liver disease. However, on-chip replicating liver physicochemical microenvironments is still a challenge. Herein, we developed a liver lobule chip with dual blood supply, achieving self-organized liver microtissue that is similar to in vivo tissue. Based on the chip, we successfully modeled NAFLD under physiologically differentiated nutrient supplies. For the first time, the changing lipid zonation in a single liver lobule with the early-stage progression of NAFLD was demonstrated on a liver chip. This study provides a promising platform for modeling liver-related diseases. Graphical abstract: Image, graphical abstract